Analisis Kepuasan Pelanggan Digitalisasi SPBU Pertamina Dengan Metode Customer Satisfaction Index di PT Telkom Akses: Analysis of Customer Satisfaction with the Digitalization of Pertamina Gas Stations Using the Customer Satisfaction Index Method at PT Telkom Akses - Damanhuri, Asep; Hastasari, Ratih (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to determine the level of customer satisfaction as well as the factors that most influence customer satisfaction toward service quality and the handling of digitalization system disruptions at Pertamina gas stations by PT Telkom Akses. The method used in this study is the Customer Satisfaction Index (CSI) method. Data were collected through the distribution of questionnaires to customers of Pertamina gas stations that partner with PT Telkom Akses, using a Likert scale as a measurement tool for the level of importance and customer satisfaction toward the service attributes provided. The results of the study indicate that the Customer Satisfaction Index (CSI) value falls into the satisfied category, which shows that, in general, customers are satisfied with the services and handling of digitalization system disruptions provided by PT Telkom Akses. The service attributes that have the greatest influence on customer satisfaction are the speed and accuracy of disruption handling, punctuality of service time, and good documentation of disruptions. The results of this study are expected to serve as evaluation material for PT Telkom Akses in improving service quality in order to maintain and enhance customer satisfaction.